A dimensão da informação no contexto dos novos direitos (ambiental e consumidor) a partir da observação do risco das novas tecnologias - Atz, Ana Paula (Universidade do Vale do Rio dos Sinos, 2011)
The society has faced in our times a high level of uncertainty and complexity, especially aggravated by the advent of high technology. In addition to their benefits, they also magnify the risks that are of global features and indivisible. The proposed work aims analyzing the extent that information plays in the field of environmental law and consumer law, from the risk communication biotechnology and nanotechnology. In this step, these new rights are in the same historical context of man, for transcending the individuality, dealing with the protection, rights and obligations of diffuse and collective. Whereas the subjects of rights is more vulnerable to the dangers and consequences arising from biotechnology and nanotechnology, are the environment and the consumer, the proposed work aims to answer the following questions: how the environmental law and consumer law manage such risks and inform the society? Still, if the risk is something that refers to the future time, how the legal system can, within this context, operational effectiveness with the formation of links with the future? To answer these questions the present study uses the contribution provided by the Theory of Social Systems, by presenting a new epistemological model, able to explain the relations of the legal system and society. For an appropriate treatment of risk, it will analyze the relations between law, science and technology in its management, as well as the importance of establishing new legal observations. It has been that this process occurs mainly by mechanisms that favor the production of information and the consequent risk communication, aimed at protecting the environment and consumers.
Keywords: Risco; Biotecnologia; Nanotecnologia; Teoria sistêmica; Dever de informar; Direito ambiental; Direito do consumidor; Responsabilidade civil; Risk; Biotechnology; Nanotechnology; Systems theory; Information environmental law; Consumer law; Civil liability; ACCNPQ::Ciências Sociais Aplicadas::Direito